1998
DOI: 10.1111/j.1744-6570.1998.tb00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Learner Effort and Goal Orientation on Two Learning Outcomes

Abstract: Training research is beginning to examine the trainee as an active participant in the learning process. One component of this process involves the choices learners make about the effort they will apply to the learning task. Learner effort was examined in two ways: amount of effort and type of effort. Both amount and type of effort were measured in multiple ways. The results indicated that mastery orientation and time on task were the strongest predictors of performance on the knowledge learning outcome, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
277
1
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(299 citation statements)
references
References 39 publications
12
277
1
9
Order By: Relevance
“…As a consequence the pattern of extraneous and germane cognitive load is rather determined. However, as Fisher and Ford (1998) have argued, the allocation of effort toward learning activities is also driven by individual motivational processes, such as personal goals and interests. For this reason, Gerjets and Scheiter (2003) have proposed an augmented model of cognitive load theory in which learner goals and processing strategies moderate between the instructional design and the pattern of cognitive load.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence the pattern of extraneous and germane cognitive load is rather determined. However, as Fisher and Ford (1998) have argued, the allocation of effort toward learning activities is also driven by individual motivational processes, such as personal goals and interests. For this reason, Gerjets and Scheiter (2003) have proposed an augmented model of cognitive load theory in which learner goals and processing strategies moderate between the instructional design and the pattern of cognitive load.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, those with an incremental theory of the self typically approach performance situations with mastery, or learning goal orientation (characterized by the desire to increase one's competence on the task) which is thought to be beneficial to learning (Dweck, 2000;Dweck & Leggett, 1988). Mastery oriented individuals have been characterized as being self-directed and selfregulated learners, they believe that ability is malleable and effort leads to success, prefer challenges, and engage in more complex learning strategies (Dweck, 2000;Dweck & Leggett, 1988;Fisher & Ford, 1998).…”
Section: Unbiased Processingmentioning
confidence: 99%
“…Early research relying on a dichotomous conceptualization of goal orientation repeatedly showed a mastery orientation to be more beneficial for a wide range of task performances than a performance orientation (e.g., Button et al, 1996;Farr et al, 1993;Ford et al, 1998;Phillips & Gully, 1997;VandeWalle, Brown, Cron, & Slocum, 1999). However, recent achievement goal research suggests that a performance orientation may also have beneficial effects, particularly with regard to actual performance.…”
Section: Goal Orientations and The Outcomes Of Job Performance And Jomentioning
confidence: 99%
“…Moreover, innovative job performance concerns the development and application of something new for which the requisite knowledge and strategies have yet to be learned. Research has shown that a mastery goal focuses an individual's attention on the elaboration and development of new knowledge and deep processing strategies leading to effectiveness in complex and unfamiliar tasks (Elliot & McGregor, 2001;Fisher & Ford, 1998;Steele-Johnson et al, 2000;Winters & Latham, 1996). Second, mastery-oriented employees have personal and intrinsic interest in the tasks they perform (Barron & Harackiewicz, 2000;Elliot, 1999;Pintrich, 2000;Van Yperen, 2003a).…”
Section: Hypothesis 2 a Performance Orientation Is Positively Relatementioning
confidence: 99%
See 1 more Smart Citation